About an observation of coccydynia treated by surgery - Noukhoum Koné (The Pan African Medical Journal, 2020)

(untitled)
Coccygodynia is pain located in coccyx. Factors that increase are stay position and stand up. Trauma seems to be his first cause, it can be falled in a sitting position, post-delivery or repeated micro-trauma. Therapeutic management depends on the mechanism involved and relies on manual treatments, infiltrations, even surgery, with good results and a success rate of about 90%. We report the case of a 23-year-old patient with disabling coccygeal pain, progressively worsening, following a fall of a floor 4 meters high, the patient sitting with reception on the buttocks. The pains have a repercussion on the sphincter function with the installation of a rather severe constipation. The examination finds an exquisite pain with regard to the sacrum on palpation without any sign of disco-radicular conflict and the skin facing is normal. The patient has tried everything in terms of conservative treatment including manipulations. The sacro-coccygeal CT shows in sagittal section (A) a dislocation of the entire coccyx compared to the 5th sacred piece. The incision arcuate (B) was preferred over the median vertical incision in the intergluteal fold closer to the anus with a non-nefiable infectious risk, ranging from 6.15 to 16.6% depending on the data from the terature. Excision of the coccyx (C) was performed under general anesthesia, the patient installed in ventral decubitus. The clinical evolution was significantly favorable.